Does the Company's Scale, Fixed Asset Intensity and Operating Cash Flow Affect Asset Revaluation? - Poerwati, Rr. Tjahjaning; Hardiningsih, Pancawati; Srimindarti, Caecilia; Sundari, Retno Ika (Jurnal Analisis Bisnis Ekonomi, 2020)
Fixed assets that are measured using cost may have lost their relevance because they do not reflect the real situation. This study aims to analyze the factors that influence the company to revaluate its fixed assets. The sample of this study consisted of 426 manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2018 time frame. The research sample was selected by purposive sampling. Technical analysis of the study used logistic regression. The results of this study found that only fixed asset intensity and operating cash flow affect the revaluation of fixed assets and the scale of the company does not affect the decision of the revaluation of fixed assets. The implication of the results of the study shows that large-scale companies do not always revaluate fixed assets because they can cause taxes on revaluations that must be borne by the company. In addition, the practical implications also show that the Indonesian government must increase the number of licensed appraisers to compensate for the increasing number of companies adopting revaluation models.